Exchange Rates, Equity Prices, and Capital Flows - Hau, Harald; Rey, Hélène (Review of Financial Studies, 2006)
We develop an equilibrium model in which exchange rates, stock prices and capital flows are jointly determined under incomplete forex risk trading. Incomplete hedging of forex risk, documented for U.S. global mutual funds, has three important implications: 1) exchange rates are almost as volatile as equity prices when the forex liquidity supply is not infinitely price elastic; 2) higher returns in the home equity market relative to the foreign equity market are associated with a home currency depreciation; 3) net equity flows into the foreign market are positively correlated with a foreign currency appreciation. The model predictions are strongly supported at daily, monthly and quarterly frequencies for 17 OECD countries visà-vis the U.S. Moreover, correlations are strongest after 1990 and for countries with higher market capitalization relative to GDP, suggesting that the observed exchange rate dynamics is indeed related to equity market development. Deniz Igan provided outstanding research assistance. Thanks also to participants in the 2002 NBER IFM summer institute, the 2003 European summer symposium in finanical markets, the FX microstructure conference at the Stockholm Institute for Finance and in seminars at Columbia, Finance sur Seine (Paris), Georgetown, George Washington University, and the IMF. We are both very grateful to the IMF Research Department for its warm hospitality and its stimulating